Direct ink writing of reaction bonded silicon carbide ceramics with high thermal conductivity. Issue 6 (15th March 2023) - Wang, Guantong; Miao, Yalan; Gong, Hongyu; Sheng, Mingming; Jing, Jie; Liu, Maoyun; Lu, Junbin; Gong, Zhigang; Ma, Kun
Abstract: Silicon carbide (SiC) ceramic is one of the most used ceramic materials due to its excellent mechanical and thermal properties but the cost is high in production. Three-dimensional (3D) manufacturing of ceramic materials provides the possibility to fabricate ceramic components with unique geometry structures and can save time and cost in producing form and function parts. In this paper, reaction bonded silicon carbide (RBSC) ceramic was fabricated through direct ink writing (DIW) technology. Reaction bonded silicon carbide (RBSC) means infiltration of carbon containing porous green parts with melting silicon, leading to form β-SiC. Remaining pores are filled by residual free silicon. Silicon carbide (SiC) based inks with different carbon black content at solid content of 36 vol% were prepared. The inks consisted of silicon carbide powder as inner filler, carbon black powder and low content sodium alginate as the binder. The effect of carbon black content on rheological behavior was studied. The results showed that the carbon black content played an important role in adjusting the viscosity, modulus and yield point. With the increasing carbon black content, shrinkage of the printed green parts decreased. When the carbon black content reached 20 wt%, the final DIW RBSC ceramics had low residual Si content. The maximum density, flexural strength and thermal conductivity were 2.91 g/cm 3, 229 MPa, and 132 W/(m·K), respectively. This study shows a bright prospect of this innovated 3D printing technology for flexibly producing complex and net-shaped RBSC ceramic parts.